2019
DOI: 10.3390/v11100898
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Avian Coronavirus Infectious Bronchitis Virus in Yellow Chickens in Southern China over the Past Decade: Revealing the Changes of Genetic Diversity, Dominant Genotypes, and Selection Pressure

Abstract: The high mutation rates of infectious bronchitis virus (IBV) pose economic threats to the poultry industry. In order to track the genetic evolutionary of IBV isolates circulating in yellow chickens, we continued to conduct the genetic analyses of the structural genes S1, E, M, and N from 64 IBV isolates in southern China during 2009–2017. The results showed that the dominant genotypes based on the four genes had changed when compared with those during 1985–2008. Based on the S1 gene phylogenetic tree, LX4-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 66 publications
4
34
0
Order By: Relevance
“…The sequences of all GVI-1 strains published in GenBank were downloaded for phylogenetic analysis, and the results indicated that the majority of GVI-1 strains were isolated from southern China, which is consistent Fig. 4 Virus recovery from oropharyngeal and cloacal swabs from chickens challenged with GDTS13 and vaccine strains of IBV with previous studies [18,20]. Although there are no data available for GVI-1 in China after 2017, the spread of GVI in southern China should not be ignored.…”
Section: Discussionsupporting
confidence: 79%
“…The sequences of all GVI-1 strains published in GenBank were downloaded for phylogenetic analysis, and the results indicated that the majority of GVI-1 strains were isolated from southern China, which is consistent Fig. 4 Virus recovery from oropharyngeal and cloacal swabs from chickens challenged with GDTS13 and vaccine strains of IBV with previous studies [18,20]. Although there are no data available for GVI-1 in China after 2017, the spread of GVI in southern China should not be ignored.…”
Section: Discussionsupporting
confidence: 79%
“…Kandeil et al [1] demonstrate a high seroprevalence of MERS coronavirus in adult dromedary camels from Asia and Africa, and Alsaadi et al [2] characterize a fusion peptide in the spike protein of MERS-CoV. Avian coronaviruses are also addressed in the article from Fan et al [3], which reveals the changes in genetic diversity, dominant genotypes, and selection pressure on the bronchitis virus (IBV) circulating in yellow chickens in China.…”
mentioning
confidence: 99%
“…An entropy value bigger than 0.6 indicates the corresponding aa-site was not conserved ( Fan et al., 2019 ). The result of analysis of entropy of gag , pol, and env genes on aa-sequences showed that the env gene had the largest variation, and this is consistent with previous studies ( Wang et al., 2018b ).…”
Section: Discussionmentioning
confidence: 99%